I Got a D in Salami - Winkler, Henry 1945-; Oliver, Lin; Heyer, Carol, 1950- (New York : Grosset & Dunlap, 2003)
Antics ensue after Hank throws his report card into a meat grinder.
Keywords: Report cards -- Fiction; Schools -- Fiction